Psychotherapists: What They Do Versus What They Say They Do - Cyr, Mireille; Bouchard, Marc-André; Lecomte, Conrad (Canadian Journal of Counselling and Psychotherapy, 2011)
Sixty-eight psychotherapists of various theoretical orientations expressed their expectations of using specific response modes to short written transcripts of therapy sessions under conditions of either high or low self-awareness. This self-rating was then correlated with three other sources of observation: (a) actual behaviour in two therapy sessions; (b) assessment ratings by peers; and (c) response modes given to written statements from three clients. Statistical analyses showed no differences between the high and low self-awareness group and no significant relationships were observed between the self-rating of the subjects and the ratings of peers, or any other measurements of therapist behaviour. Implications of these results are discussed in terms of variables mediating the self-reports and the importance of process expectations as a common factor in psychotherapy.